The incidence, clinical outcome, and protective factors of mixed chimerism following hematopoietic stem cell transplantation for severe aplastic anemia. Issue 2 (20th January 2021) - Xu, Zheng‐Li; Cheng, Yi‐Fei; Zhang, Yuan‐Yuan; Mo, Xiao‐Dong; Han, Ting‐Ting; Wang, Feng‐Rong; Yan, Chen‐Hua; Sun, Yu‐Qian; Chen, Yu‐Hong; Tang, Fei‐Fei; Han, Wei; Wang, Yu; et al.
Abstract: Objectives: The aim of our study was to determine possible predictors and clinical course of mixed chimerism (MC) in aplastic anemia after transplantation. Methods: A total of 207 transplants were obtained from haploidentical donors (HID) using busulfan (Bu), cyclophosphamide (Cy), and anti‐thymocyte globulin (ATG) regimens, and 69 transplants from matched related donors (MRD) and 29 transplants from unrelated donors (URD) using Cy/ATG regimens were obtained. Results: Incidences of MC were 1.93 ± 0.01%, 20.29 ± 0.01%, and 35.71 ± 0.01% in HID, MRD, and URD transplantation ( p < .001). In multivariate analysis, incidence of MC was significantly higher in patients without adding Bu in conditioning ( p < .001) and receiving a lower number of CD3 + cells in graft ( p = .042). MC was associated with significantly lower II‐IV aGvHD (3.70% vs. 27.7%, p = .007), but higher secondary graft rejection rates (14.8% vs. 0.4%, p < .001) and poorer overall survival (72.7 ± 8.9% vs. 89.6 ± 2.0%, p = .011) than those of donor chimerism cohort. Conclusions: Mixed chimerism was an unsettling status even in non‐malignancy. Haploidentical transplantation with more intense regimen by adding Bu to Cy and ATG was associated with reduced MC following HSCT for SAA. An intensified regimen should be explored in matched related or unrelated donors.